Automated Feeding System for Aquariums based on the Internet of Things - Irfan Setiawan; Purba Daru Kusuma; Ashridini Maharawati (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
Feeding is influential for the survival of fish in the aquarium environment. Until now, most people do manual feeding. With manual feeding, the aquarium owner often forgets to feed the fish in the aquarium, whether it's too little or too much, both in terms of scale or timing of the feeding. In addition, if the aquarium owner is doing activities outside the home, the fish will not get food. This study adopts descriptive and casual methods. The first one is used to describe the system concept and the system design plan used. This fish-feeding system with NodeMCU ESP8266 based on the Internet of Things (IoT) can be implemented to control the feeding of fish in an aquarium environment. The purpose of this automatic feeding system is to ensure that the feed given to the fish in the aquarium is evenly distributed. Feeding the fish unevenly will cause the aquarium water to become cloudy. Turbid water can cause the ornamental fish in it to die besides being unpleasant to look at. Based on the results of testing the accuracy of the distance between the ruler and the ultrasonic sensor 5 times, an average error of 1.795% was found. In other words, the success of the ultrasonic sensor in detecting the distance of objects (fish) is 98.205%.